Genetic Based EFL Classroom Management - Roslina (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2021)
This article was inspired by Jamil Pooniran's concept of STIFIn genetic intelligence and language learning methodology, especially regarding classroom management. All of these inspirations became the author's reference for pursuing his mind in building a genetic-based EFL classroom management concept. This article was not based on empirical data. Still, it was built and constructed from the previous concept, namely the STIFIn concept of genetic intelligence, which was synthesized into a genetic-based class management concept for the EFL class. This study aimed to determine how to apply the concept of genetic-based classroom management to the EFL class. Based on the STIFIn concept of genetic intelligence, the authors formulated a genetic-based classroom management concept for EFL classes adapted for EFL students' five types of machine intelligence. In summary, the author concluded that the genetic-based classroom management concept for the EFL class could be applied to the three managerial class phases, namely involving stage and using calibration at the evaluation stage.